Incidence and prevalence of falls in adults with intellectual disability living in the community: a systematic review protocol - Ho, P.; Patman, S.; Bulsara, C.; Downs, Jennepher; Bulsara, M.; Hill, Anne-Marie (The University of Adelaide, 2017)
The objective of this review is to synthesize the best available evidence to determine the incidence and prevalence of falls among adults with intellectual disability (ID) living within the community.